Impact of Board Size, Profitability, Public Ownership, and Media Exposure on CSR Disclosure - Budiyani, Luh Ayu Sri; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 34 No 5 (2024)DO - 10.24843/EJA.2024.v34.i05.p17, 2024)
CSR disclosure serves as a mechanism for companies to communicate their social and environmental impacts to stakeholders. This study investigates the correlation between profitability, public ownership, media exposure, and board size with CSR disclosure, grounded in legitimacy theory. Utilizing the purposive sampling method, the study examines 150 observations from food and beverage companies listed on the Indonesia Stock Exchange for 2018-2022 period. Data were analyzed using multiple linear regression. The findings reveal no significant relationship between profitability, public ownership, and media exposure with CSR disclosure. However, board size demonstrates a positive association with CSR disclosure. These results underscore that among the variables studied, only the board of comissioners size positively relates to CSR disclosure practices. Keywords: Profitability; Public Ownership; Size of The Board Of Comissioners; Media Exposure; CSR Disclosure